FACTORS ASSOCIATED WITH THE ADHERENCE TO ANTI-RETROVIRAL THERAPY AMONG PREGNANT MOTHERS ATTENDING THE ART CLINIC AT CHINA-UGANDA FRIENDSHIP HOSPITAL, NAGURU. A DESCRIPTIVE CROSS-SECTIONAL STUDY. - Habasa, Hudson (Student’s Journal of Health Research Africa, 2023)
Purpose of the study: The purpose of the study was to assess the factors associated with adherence to Anti-Retroviral Therapy among pregnant mothers attending the ART clinic at China Uganda Friendship Hospital, Naguru To assess the knowledge, demographic factors, and socio-economic factors associated with the adherence to Anti-retroviral therapy among pregnant mothers attending the ART clinic at China-Uganda Friendship Hospital, Naguru. Method: The descriptive cross-sectional study was carried out from November 2022 to January 2023 where study data was collected at once and there were no follow-up of respondents after the study. The participants in the study were selected using a purposive sampling method. Open and close-ended questionnaires were used in data collection. Results: Many (55.9%) of the well-adherent mothers were 30 years and above. The majority (97%) of the well-adherent mothers were urban dwellers. The majority (60%) of the respondents earned less than Ush500,000 per month while the minority (7%) earned above Ush300,000 per month. Mothers with a relatively high monthly income were found to adhere better than those with a low monthly income. A majority (96.8%) of the well-adherent respondents had good social support. Conclusion: Knowledge about ART adherence and PMTCT is associated with the level of adherence to ART among pregnant mothers attending the ART clinic at China-Uganda Friendship Hospital, Naguru. Demographic factors such as the respondent’s age, place of residence, and level of education were found to be associated with ART adherence. The mother’s financial status, social support, and HIV-associated stigma were some of the socioeconomic factors found to be associated with the adherence to ART. Recommendations: Consistent attendance of routine health education and counseling, prescription of drugs for quite a long duration, male partner involvement, and starting up of small scale income generating projects should be advocated for to improve medication adherence.